PERAN GURU PAI DALAM MEMBENTUK KECERDASAN INTELEKTUAL DAN SPIRITUAL SISWA DI MTs PROBOLINGGO - Mohammad Hidayatullah; Azhar haq; Yorita Febry Lismanda (VICRATINA, 2019)
Education has a very important role in maintaining the existence of every nation in the world throughout the ages. Education is crucial for the creation of a better civilization of society, for which the realization of a quality society is the responsibility of education. This study aims to determine the role of PAI teachers in shaping the intellectual and spiritual intelligence of students at MTs Darul Musthofa Probolinggo. The focus of the problem to be studied is the role of the teacher in developing intellectual and spiritual intelligence in students at MTs Darul Musthofa Probolinggo. 2) aspects of intellectual and spiritual intelligence of students in learning Islamic Religion at MTs Darul Musthofa Probolinggo. 3) supporting and inhibiting factors in developing intellectual and spiritual intelligence of students in PAI learning at MTs Darul Musthofa Probolinggo. This research is a type of qualitative research. The research subject was the role of PAI teachers. Data collection techniques using the method of observation, interviews, and documentation. The data analysis technique uses three main components, namely data reduction, data display, and data verification. From the results of the study concluded that the role of PAI teachers in shaping intellectual and spiritual intelligence of students who are highly competitive and have good character in the school environment and society.